A comprehensive care program achieves high remission rates in rheumatoid arthritis in a middle-income setting. Experience of a center of excellence in Colombia (2018)
Management of rheumatoid arthritis (RA) in many Latin-American countries is impaired by fragmentation and scarce healthcare provision, resulting in obstacles to access, diagnosis, and treatment, and consequently in poor health outcomes. The aim of this study is to propose a comprehensive care program as a model to provide healthcare to RA patients receiving synthetic DMARDs in a Colombian setting by describing the model and its results. Health outcomes were prospectively collected in all patients entering the program. By protocol, patients are followed up during 24 months using a treat-to-target strategy with a patient-centered care (PCC) model, meaning that a patient should be seen by rheumatologist, physical and occupational therapist, physiatrist, nutritionist and psychologist, at least three times a year according to disease activity by DAS28. Otherwise, patients receive standard therapy. The incidence of remission and low disease activity (LDA) was calculated by periods of follow-up. A total of 968 patients entered the program from January 2015 to December 2016; 80.2% were women. At baseline, 41% of patients were in remission, 17% in LDA and 42% in MDS/SDA. At 24 months of follow-up, 66% were in remission, 18% in LDA and only 16% in MDS/SDA. Regarding DAS28, the mean at the beginning of the time analysis was 3.1 (SD 1.0) and after 24 months it was 2.4 (SD 0.7), showing a statistically significant improvement (p < 0.001). In all patients, the reduction of disease activity was 65% (95% CI, 58–71). Patients entering the PCC program benefited from a global improvement in disease activity in terms of DAS28.